2022
DOI: 10.1021/acsanm.2c01144
|View full text |Cite
|
Sign up to set email alerts
|

Highly Photoluminescent Yb-Doped CsPbBrI2 Nanocrystals in Ethylene Vinyl Acetate Composite Films for Wide Color Gamut Backlight Displays

Abstract: Metal halide CsPbX 3 (X = Cl, Br, I) perovskite nanocrystals (NCs) have been widely studied because of their high photoluminescent quantum yield (PLQY) and tunable emission wavelength. However, their weak hydrothermal stability greatly limits the use of CsPbX 3 NCs under harsh conditions. This work successfully solved the problem of poor stability of CsPbX 3 NCs through the ethylene vinyl acetate (EVA) film coating strategy and expanded the application range of CsPbX 3 NCs. In addition, we demonstrated an impr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 43 publications
(71 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, KBr modification passivates surface defects, leading to a decrease in non-radiative recombination centers and fostering higher PLQY. However, an excessive amount of KBr may introduce new defects, potentially undermining PLQY [23].…”
Section: Resultsmentioning
confidence: 99%
“…Furthermore, KBr modification passivates surface defects, leading to a decrease in non-radiative recombination centers and fostering higher PLQY. However, an excessive amount of KBr may introduce new defects, potentially undermining PLQY [23].…”
Section: Resultsmentioning
confidence: 99%
“…Different from the deep traps, shallow traps facilitate an increase in electron density in the conduction band of the perovskite host and, hence, may lead to PL enhancement. Zhou et al showed that Yb-doping can increase the PL QY from 30 to 50% for CsPbBrI 2 pNCs [ 49 ]. Doping with divalent Yb 2+ ions can also result in the improvement of the environmental and thermal stability of perovskite materials, as was shown for Yb 2+ -alloyed CsPb 1−x Yb x I 3 pNCs [ 50 ].…”
Section: Optical Propertiesmentioning
confidence: 99%